(untitled) (Neo Science Peer Reviewed Journal, 2023)
The article examines the pedagogical conditions for the formation of aesthetic culture of students as the most important component of the spiritual image of the individual, which is especially important in modern conditions of intensive growth of the industrial and technological sphere, informatization and computerization of society.